Design and Simulation of a Fully Digitized GNSS Receiver Front-End - Yuan Yu; Qing Chang; Yuan Chen (Discrete Dynamics in Nature and Society)
In the near future, RF front-ends of GNSS receivers may become very complicated when multifrequency signals are available from at least four global navigation systems. Based on the direct RF sampling technique, fully digitized receiver front-ends may solve the problem. In this paper, a direct digitization RF front-end scheme is presented. At first, a simplified sampling rate selection method is adopted to determine the optimal value. Then, the entire spectrum of GNSS signal is directly digitized through RF sampling at a very fast sampling rate. After that, the decimation and filtering network is designed to lower the sampling rate efficiently. It also realizes the digital downconversion of the signal of interest and the separation of narrow band signals from different navigation systems. The scheme can be flexibly implemented in software. Its effectiveness is proved through the experiment using simulated and true signals.